Strategi Komunikasi Politik Perempuan di Lembaga Legislatif - Mukarom, Zaenal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
The involvement of women role in legislative institution can be said so minim. This condition caused by several factors: (1) culture of national politics communication nuance patrimonial, (2) domestics roles as regulating of family in home, care, parenting and education to child and moral fortress. As a effort to improve women role in politics needed strategy steps done by women them selves throught counter of political communication and strategy tergetted by political party as: prepare generation from women and to be meanstream to women in society